Influence of Gag-protease-mediated replication capacity on disease progression in individuals recently infected with HIV-1 subtype C. - Wright, J; Novitsky, V; Brockman, M; Brumme, Z; Brumme, C; Carlson, J; Heckerman, D; Wang, B; Losina, E; Leshwedi, M; van der Stok, M; Maphumulo, L; et al. (2011)
HLA class I-mediated selection of immune escape mutations in functionally important Gag epitopes may partly explain slower disease progression in HIV-1-infected individuals with protective HLA alleles. To investigate the impact of Gag function on disease progression, the replication capacities of viruses encoding Gag-protease from 60 individuals in early HIV-1 subtype C infection were assayed in an HIV-1-inducible green fluorescent protein reporter cell line and were correlated with subsequent disease progression. Replication capacities did not correlate with viral load set points (P = 0.37) but were significantly lower in individuals with below-median viral load set points (P = 0.03), and there was a trend of correlation between lower replication capacities and lower rates of CD4 decline (P = 0.09). Overall, the proportion of host HLA-specific Gag polymorphisms in or adjacent to epitopes was negatively associated with replication capacities (P = 0.04), but host HLA-B-specific polymorphisms were associated with higher viral load set points (P = 0.01). Further, polymorphisms associated with host-specific protective HLA alleles were linked with higher viral load set points (P = 0.03). These data suggest that transmission or early HLA-driven selection of Gag polymorphisms results in reduced early cytotoxic T-lymphocyte (CTL) responses and higher viral load set points. In support of the former, 46% of individuals with nonprotective alleles harbored a Gag polymorphism exclusively associated with a protective HLA allele, indicating a high rate of their transmission in sub-Saharan Africa. Overall, HIV disease progression is likely to be affected by the ability to mount effective Gag CTL responses as well as the replication capacity of the transmitted virus.